2017
DOI: 10.1002/slct.201700448
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis of Cyclic Nitrones via Organocatalytic Michael Addition of Aldehydes to Nitroolefins and Subsequent Reductive Cyclization.

Abstract: A direct approach to the synthesis of optically active fivemembered cyclic nitrones is described. The presented strategy is based on organocatalytic Michael addition of aldehydes to trans-nitroalkenes and subsequent reductive cyclization. The developed methodology was successfully applied to the asymmetric synthesis of Methdilazine.[a] Dr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
(6 reference statements)
0
6
0
Order By: Relevance
“…The γ‐nitroaldehydes with high syn/anti ratio react with the catalyst, a low steady‐state concentration of the enamine is rapidly established, and the equilibration between syn and anti continues until thermodynamic ratio is reached (Scheme ). This effect, intensively studied and explained by Blackmond, has been confirmed by our group …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The γ‐nitroaldehydes with high syn/anti ratio react with the catalyst, a low steady‐state concentration of the enamine is rapidly established, and the equilibration between syn and anti continues until thermodynamic ratio is reached (Scheme ). This effect, intensively studied and explained by Blackmond, has been confirmed by our group …”
Section: Resultsmentioning
confidence: 99%
“…Very recently, we demonstrated that functionalized, optically active cyclic nitrones or pyrrolidines can be obtained in a simple and highly efficient manner via organocatalytic Michael addition of aldehydes to trans ‐nitroalkenes and subsequent reductive cyclization . This methodology was successfully applied, as a key step in the asymmetric total synthesis of methdilazine, BZN molecule, and asenapine.…”
Section: Introductionmentioning
confidence: 99%
“…Aldehydes having R 2 =Et and Ph decreased the yield and ee (Scheme 7). [54] An important asymmetric Michael addition reaction was documented by Thomas C. Nugent et al in 2017. Employing 10 mol % of amino acid-derived L-serine based catalyst 28, the reaction of α-branched cyclohexane-carboxaldehyde 25 with 4hydroxy nitrostyrene 26 in the presence of 15 mol % of KOH provided Michael product 27 with high ee.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the same organocatalysts, in the presence of p -nitrophenol as co-catalyst, has been employed in the asymmetric reaction of succinaldehyde with 3-bromo-2-fluoronitrostyrene, to give a key intermediate in the total synthesis of the prostaglandin-analog beraprost [ 43 ]. Moreover, γ-nitroaldehydes type 2 have been prepared organocatalytically by means of 13 , and have been used for the synthesis of enantioenriched five-membered cyclic nitrones after reductive cyclization [ 44 ].…”
Section: Carbon Nucleophilesmentioning
confidence: 99%